2005
DOI: 10.1002/jmri.20402
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of regional airways obstruction using dynamic hyperpolarized 3He MRI—Preliminary results in children with cystic fibrosis

Abstract: Purpose: To investigate regional airways obstruction in patients with cystic fibrosis (CF) with quantitative analysis of dynamic hyperpolarized (HP) 3 He MRI. Materials and Methods:Dynamic radial projection MRI of HP 3 He gas was used to study respiratory dynamics in a group of eight children with CF. Signal kinetics in a total of seven regions of interest (ROIs; three in each lung, and one in the trachea) were compared with the results of spirometric pulmonary function tests (PFTs). The tracheal signal inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
2

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 25 publications
1
61
1
2
Order By: Relevance
“…In a small group of eight children with cystic fibrosis, comparison of He-3 imaging with functional measures of airway obstruction showed good correlation and also that children are able to tolerate helium imaging (Koumellis et al 2005). He-3 MRI has also been used to assess regional patterns of airway closure in asthma (Altes et al 2001;de Lange et al 2006).…”
Section: (B ) Clinical Applicationsmentioning
confidence: 97%
“…In a small group of eight children with cystic fibrosis, comparison of He-3 imaging with functional measures of airway obstruction showed good correlation and also that children are able to tolerate helium imaging (Koumellis et al 2005). He-3 MRI has also been used to assess regional patterns of airway closure in asthma (Altes et al 2001;de Lange et al 2006).…”
Section: (B ) Clinical Applicationsmentioning
confidence: 97%
“…3) (68) and CF (80). Semiquantitative approaches using the regional slope of gas uptake normalized to the uptake in the trachea have also been applied to CF (81). At present, dynamic techniques are 2D and are performed with a second inhalation of HP gas in which the first inhalation is used for static ventilation imaging as described above.…”
Section: Dynamic Ventilation Imaging (Respiratory Dynamics)mentioning
confidence: 99%
“…These preliminary studies showed regional patterns of obstruction that correlated with FEV 1 . The goal of this regional approach is early detection and evaluation of small airway disease for more sensitive and specific detection of disease progression and response to therapy (81).…”
Section: Cfmentioning
confidence: 99%
“…3-Helium ( 3 He) MRI of the lungs is a powerful tool for assessing gas distribution and lung function, and ventilation defects in adults and children with CF have been previously reported (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%